The 2009 European elections in Portugal: primaries or simply second order? - Freire, A. (Portuguese Journal of Social Science, 2010)
The 2009 European Parliament elections were especially interesting for the Portuguese media, politicians and citizens because they took place shortly before the legislative and local elections of 27 September and 11 October 2009, respectively. Because of this proximity, the elections to the European Parliament were seen as a kind of primary for the forthcoming national elections. However, this also gave them special relevance in terms of electoral behaviour research concerning second-order elections. Here we reflect on these issues, not only by looking at the last European Parliament elections from a longitudinal perspective, but also by comparing the result with what happened in the following national elections. Since 1987 there have been major changes in the Portuguese party system, with the emergence of a majoritarian trend that was first visible in the legislative elections but which has since been replicated in European and local elections. However, the 2009 European elections showed a significant increase in party system fragmentation, indicating a possible return to the ‘consensual’ period (1975–87). The questions are thus: to what extent may this be an indication of a major structural change; and is it simply a response to specific political circumstances?